PENGARUH PERUBAHAN TEMPERATUR ATMOSFER TERHADAP JARAK TERBANG MAKSIMUM PESAWAT N219 PADA FASE TERBANG JELAJAH - Gita Kusumastuti; Hary Sutjahjono; Dedi Dwilaksana (STATOR: Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
N219 aircraft as a plane that is still in the test flight period needs to be evaluated and refined in various fields, one of them is performance. Performance examines the achievements of flying like the maximum range that plane can take using the available fuel capacity. To determine the effect of atmospheric condition on the performance of flying then in this study given the variation of atmospheric temperature that is on the condition ISA 0, ISA+10, ISA+20, and ISA+30. Cruise is the focus of the study because this flight phase is the dominant in terms of distance, time, and fuel consumption. The method used is specific fuel consumption method. This method is used to determine the speed that can generate the maximum range. The purpose of this study was to investigate the effect of atmospheric temperature changes on the maximum range of N219 aircraft in the cruising phase. The results show that maximum range of aircraft increases with increasing temperature to the condition of ISA 0. Maximum range at ISA 0 is 1.946,48 km and continous to increase until 2.224,36 km at ISA+30. This is due to the decrease in air density by increasing atmospheric temperature to ISA 0, causing the increase in the specific air range, thus increasing the maximum range of aircraft. Keywords: Pesawat N219, specific air range, cruise